â€œDrug Release Kinetic Modeling and Gamma Scintigraphic Studies of Dual Ca2+ and SO4 2- Cross-linked Microbeads for Colon Specific Targetingâ€ (Asian Journal of Pharmaceutics (AJP), 2020)
Objectives: Ionic gelation-based polyelectrolyte complexes of blend chitosan-sodium alginate polysaccharidesbased microbeads of methotrexate were prepared by dual cross-linkages with divalent Ca2+ and SO4-2 ions forcolon targeting. Materials and Methods: Those developed dual cross-linked formulations were characterizedfor particle size, entrapment studies, drug content, swelling degree, etc. Results: The surface morphology resultsshowed that the optimized formulations were semi-spherical and rough-surfaced. The in vitro drug release carriedout in various simulated fluids at various pH had shown lesser release profiles in acidic media as compared toalkaline media at the end of 24 h studies. A significant drug release (P > 0.05) was observed in colonic fluidscontaining 2 and 4% w/v rat cecal as compared with control. In vivo targeting ability for the colon-specific regionwas established through gamma scintigraphic imaging technique. Differential scanning calorimetry and X-raydiffraction analysis further confirms for semi-crystalline and complete cross-linking state. The release profileand mathematical kinetic modeling revealed for anomalous non-Fickian type formulations were best fitted withHiguchi and Hixson-Crowell model, respectively. Conclusion: It can be concluded that the optimized formulationsmay be effective for colon targeting and promising to achieve drug targeting for colorectal cancer.